1993
DOI: 10.1002/j.1460-2075.1993.tb06026.x
|View full text |Cite
|
Sign up to set email alerts
|

Both Arabidopsis TATA binding protein (TBP) isoforms are functionally identical in RNA polymerase II and III transcription in plant cells: evidence for gene-specific changes in DNA binding specificity of TBP.

Abstract: Promoters of pol II and pol III transcribed U‐snRNA genes in plants have identical sequence elements comprised of a −30 TATA box and an upstream sequence element (USE), located four or three helical turns upstream of the TATA box in pol II and pol III genes, respectively; it is this difference in element spacing that determines the RNA polymerase specificity of the gene. We are interested in identifying factors binding to U‐snRNA gene promoters and their role in selection of RNA polymerase. In this work we hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 64 publications
0
23
0
Order By: Relevance
“…2C). Mutations in the TATA box element shown previously to inactivate U6 gene expression in plant protoplasts (26,27) also caused 7SL gene activity to drop to virtually undetectable levels (TATA-Dn; Fig 2B, lane 3). Mutation of the USE and TATA elements simultaneously produced a similar effect to the TATA mutant alone (USE+TATA-Dn; Fig.…”
Section: Sequence Analysismentioning
confidence: 55%
See 1 more Smart Citation
“…2C). Mutations in the TATA box element shown previously to inactivate U6 gene expression in plant protoplasts (26,27) also caused 7SL gene activity to drop to virtually undetectable levels (TATA-Dn; Fig 2B, lane 3). Mutation of the USE and TATA elements simultaneously produced a similar effect to the TATA mutant alone (USE+TATA-Dn; Fig.…”
Section: Sequence Analysismentioning
confidence: 55%
“…Mutation of the TATA box results in complete inactivation of the gene in transfected protoplasts. The same mutation was previously shown to abolish Arabidopsis U6 gene transcription in vivo (26,27). While the point mutations made in the USE sequence of At7SL-2 were not previously tested in pol Ill-specific U-snRNA genes, it has been observed that a different point mutation in the USE had similar effects on both pol II and pol III U-snRNA transcription in plant protoplasts (33).…”
Section: -Gsmentioning
confidence: 86%
“…This TBP derivative (TBP^g) has a relaxed DNA-binding spec ificity and recognizes both a canonical TAT AAA box and an altered TGTAAA box (Strubin and Struhl 1992). The combination of TEP^s and the TGTAAA box circum vents the activity of endogenous wild-type TBP in yeast (Strubin and Struhl 1992), plant (Heard et al 1993), and mammalian (Keaveney et al 1993) cells and thus allows the effects of in vitro manipulations in TBP to be exam ined in vivo.…”
Section: Experimental Designmentioning
confidence: 99%
“…Mot1 associates with Pol III promoters, although the Mot1/ TBP occupancy ratio is low. Although biochemical analysis indicates that repression by Mot1 is specific for Pol II promoters (4), Pol III promoters often have consensus TATA elements that affect transcription via the specific DNA-binding activity of TBP (19,54). Interestingly, Mot1 associates with the SNR6 and five tRNA promoters at a level that is comparable to that observed at FBA1, a strong Pol II promoter (Fig.…”
mentioning
confidence: 96%